2000
DOI: 10.1111/j.1528-1157.2000.tb01512.x
|View full text |Cite
|
Sign up to set email alerts
|

The Stigma of Epilepsy: A European Perspective

Abstract: Summary:Purpose: To study the stigma of epilepsy in a European sample.Methods: Clinical and demographic details and information about patient-perceived stigma was collected by using selfcompleted questionnaires mailed to members of epilepsy support groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
196
11
29

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(251 citation statements)
references
References 26 publications
15
196
11
29
Order By: Relevance
“…The initial diagnosis of epilepsy can cause adjustment disorders, refractory epilepsy can challenge coping resources, and epilepsy can give rise independence and social functioning [2][3][4]. Having epilepsy is associated with perceived stigma, especially in the presence of comorbid mood disorders and low self-esteem [5,6]. This means that there are many aspects of living with epilepsy, which could be considered targets for psychological treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The initial diagnosis of epilepsy can cause adjustment disorders, refractory epilepsy can challenge coping resources, and epilepsy can give rise independence and social functioning [2][3][4]. Having epilepsy is associated with perceived stigma, especially in the presence of comorbid mood disorders and low self-esteem [5,6]. This means that there are many aspects of living with epilepsy, which could be considered targets for psychological treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The risk for psychiatric disorders in people with epilepsy have been reported to be three to six times higher than observed in age matched apparently healthy population [1,15,18]. It has also been documented that children and adolescents with epilepsy experience more emotional and behavioural problems than healthy controls and others with chronic conditions [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 96%
“…Both epilepsy and depression are characterized by a chronic course and poor long-term psychosocial outcome [2]. Authors have identified psychiatric syndromes such as anxiety, depression, and behavioural affective and conversion disorders in people with epilepsy [8][9][10][11][12][13][14][15][16][17][18]. The risk for psychiatric disorders in people with epilepsy have been reported to be three to six times higher than observed in age matched apparently healthy population [1,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…Stigma researchers have Open Journal of Psychiatry generally characterized stigma as either felt or enacted [11] [12]. Enacted stigma manifests as discrimination against the stigmatized person imposed by others, whereas felt stigma is the fear of enacted stigma experienced by the stigmatized person [10]. Felt stigma may result in the stigmatized person intentionally avoiding contact with others in an attempt to avoid enacted stigma [17].…”
Section: Introductionmentioning
confidence: 99%
“…Misinformation and negative attitudes towards epilepsy contribute to the manifestation of discrimination against individuals with the condition [8]. The stigma associated with epilepsy impacts negatively on the quality of life of the sufferers [1] [9] [10]. However, the extent and the manifestations of stigma vary from one locality to another as well as with clinical contexts and social status of the individual [2] [11] [12].…”
Section: Introductionmentioning
confidence: 99%